Sellaphora labernardierei (Sellaphoraceae, Bacillariophyta), a new epilithic species from French spring and four new combinations within the genus Sellaphora - Beauger, Aude; Wetzel, Carlos E.; Voldoire, Olivier; Garreau, Alexandre; Ector, Luc (Phytotaxa, 2016)
During a floristic survey of freshwater springs in the French Massif Central region, a new Sellaphora species (Bacillariophyceae) was found and is hereby described: Sellaphora labernardierei sp. nov. This new small species, with linear to linear-elliptical valves, slightly inflated in the middle, is formally described using light and scanning electron microscopy. The species has a single H-shaped chloroplast and striae usually biseriate tending to be uniseriate near the centre of the valve. The valve dimensions, the valve, pole and central area shapes, and the striae density and pattern allow their separation from similar taxa belonging to the genera Eolimna, Naviculadicta and Sellaphora. The ecological preferences of Sellaphora labernardierei are mineral waters with high nitrate concentrations. The examination of similar taxa belonging to the genera Eolimna and Naviculadicta and their characteristics lead to propose four new combinations of Sellaphora species.